2019
DOI: 10.1016/j.joto.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of asymptomatic otitis media with effusion in patients with adenoid hypertrophy

Abstract: Objective Clinical symptoms of otitis media with effusion are rarely brought forward to the guardians of young children who the disease is most prevalent in. This often leads to poor scholastic performances and difficult social interactions. The objective of this study was to identify asymptomatic cases of otitis media with effusion present in individuals with adenoid hypertrophy. Material and Methods In a cross sectional study advocated in Justice K.S.Hegde Hospital, Karnataka India we evaluated one hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
(25 reference statements)
2
20
0
2
Order By: Relevance
“…Ren et al, 14 found middle ear effusion in 75.4% Sarwar et al 15 found middle ear effusion in 58.33%. Bhat et al 17 found 36% had either unilateral or bilateral middle ear effusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al, 14 found middle ear effusion in 75.4% Sarwar et al 15 found middle ear effusion in 58.33%. Bhat et al 17 found 36% had either unilateral or bilateral middle ear effusion.…”
Section: Discussionmentioning
confidence: 99%
“…And there was no statistically significant correlation between the presence of OME and adenoid hypertrophy. Bhat et al, 17 in a study with 100 patients, found 56% had grade 3 and 44% had grade 4 adenoid hypertrophy, mean hearing loss in patients with effusion was around 24 dB. Hearing status of the patients in the study of Syed et al, 18 in his study with children with hearing loss, found statistically significant association between adenoid hypertrophy with choanal obstruction and abutment of eustachian tube opening seen on endoscopy with hearing loss (p = 0.025).…”
Section: Discussionmentioning
confidence: 99%
“…In their study among the children with adenoid hypertrophy, Bhat et al found asymptomatic middle ear dysfunction in 36% of the study population. 13 Another study found more than 60% of episodes of symptomatic URI among young children were complicated by Acute Otitis Media or middle ear effusion. 14 These asymptomatic middle ear dysfunction may eventually progresses to full blown OME, affecting the hearing of the child and consequently language development (in early childhood).…”
Section: Discussionmentioning
confidence: 99%
“…The COM group had higher-grade biofilm formation in comparison to another group [ 27 ]. The study of Bhat et al showed that 36 of 100 pediatric with adenoid hypertrophy had the asymptomatic OME [ 28 ]. The presence of biofilms on the adenoid surface may maintain chronic illness leading to possible missed complication cases.…”
Section: Discussionmentioning
confidence: 99%